<DATA REPORT>RIOMETER RECORDS OF 30 MHz COSMIC NOISE AT SYOWA STATION, ANTARCTICA IN 1981 - OSE, Masami; KURIHARA, Noriyuki (National Institute of Polar Research, 1983)
P(論文) departmental bulletin paper